2021
DOI: 10.1111/tpj.15592
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association identifies candidate genes for drought tolerance in coast redwood and giant sequoia

Abstract: Drought is a major limitation for survival and growth in plants. With more frequent and severe drought episodes occurring due to climate change, it is imperative to understand the genomic and physiological basis of drought tolerance to be able to predict how species will respond in the future. In this study, univariate and multitrait multivariate genome-wide association study methods were used to identify candidate genes in two iconic and ecosystem-dominating species of the western USA, coast redwood and giant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…Thus, our results emphasize the contribution of phenotypic plasticity to leaf trait variation in F. crenata. Similar results were obtained in a common garden experiment conducted on Sequoia sempervirens and Sequoiadendron giganteum, where within-crown trait variation was greater than across genotypes (De La Torre et al, 2022).…”
Section: Variation Of Lma and Associated Anatomical Traitssupporting
confidence: 81%
“…Thus, our results emphasize the contribution of phenotypic plasticity to leaf trait variation in F. crenata. Similar results were obtained in a common garden experiment conducted on Sequoia sempervirens and Sequoiadendron giganteum, where within-crown trait variation was greater than across genotypes (De La Torre et al, 2022).…”
Section: Variation Of Lma and Associated Anatomical Traitssupporting
confidence: 81%
“…Other genes related to water stress response were activated (water-stress inducible 1, partial, probable carboxylesterase 15, Cao et al., 2019 , linked to drought stress response in Abies alba Behringer et al., 2015 ), including, again, protein phosphorylation (receptor kinase HAIKU2, associated with drought tolerance in Sequoia sempervirens , de la Torre et al., 2022 ), similar to the immediate drought treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both had implicit assumptions that most traits of interest would be controlled by relatively few genes—assumptions bolstered by moderate to high predicted heritabilities for traits of interest. In reality, most variants associated with these highly heritable traits have exhibited small effect sizes indicating that the genetic architecture of most quantitative traits (which most ecologically important traits are) is likely polygenic (Bresadola et al, 2019 ; Chhetri et al, 2019 ; de la Torre et al, 2021 , 2022 ; Lind et al, 2018 ). This may also be true for extended phenotypes, such as associated insect communities.…”
Section: Discussionmentioning
confidence: 99%
“…A similar story has been unfolding for forest tree species (Ingvarsson & Street, 2011 ). Most forest tree GWA studies have identified relatively low numbers of significant loci, explaining a small proportion of variation in highly heritable quantitative traits (Barker et al, 2019 ; Bresadola et al, 2019 ; de la Torre et al, 2021 , 2022 ; Fahrenkrog et al, 2017 ; Hallingbäck et al, 2019 ; Lind et al, 2018 ; McKown et al, 2018 ) with rare exceptions (Wang et al, 2018 ). Several studies have begun to employ modified and complementary methods to address potential sources of “missing heritability,” following the lead of human genomics research.…”
Section: Introductionmentioning
confidence: 99%